Acetaminophen Inhibits Fatty Infiltration without Impairing Tendon-Bone Interface Healing in a Rat Model of Acute Rotator Cuff Repair - Yoon, Jong Pil; Park, Sung-Jin; Kim, Dong-Hyun; Choi, Yoon Seong; Lee, Hyun Joo; Kim, Jun-Young; Cho, Chul-Hyun; Chung, Seok Won (Clinics in orthopedic surgery, 2025)
Background: Rotator cuff (RC) tears are a common shoulder disorder associated with pain, dysfunction, and progressive muscle degeneration. Postoperative muscle atrophy and fatty infiltration are key factors contributing to poor healing outcomes, increased rerupture rates, and long-term functional impairment. While acetaminophen (APAP) is widely used for pain management, its potential effects on muscle fatty infiltration and tendon-bone interface (TBI) healing remain unclear. This study aimed to investigate whether APAP influences fatty infiltration and TBI healing after RC surgery. We hypothesized that APAP would reduce fatty infiltration by downregulating peroxisome proliferator-activated receptor gamma (PPAR-γ) while preserving histological and biomechanical TBI integrity. Methods: A RC repair rat model was created using 12-week-old male Sprague-Dawley rats. Ten rats in the APAP group received an oral dose of 30 mg/kg APAP daily for 4 weeks after RC tendon transection, and 10 rats in the control group were administered only 0.9% saline. All rats were sacrificed 4 weeks after surgery. Fatty infiltration was analyzed qualitatively and quantitatively in the proximal part of the supraspinatus muscle. TBI was evaluated for RC healing effect through general tissue staining and biomechanical strength measurements. Results: Four weeks after tendon repair, the APAP group showed significant prevention of supraspinatus fatty infiltration compared to the control group (p < 0.001). These results were confirmed through immunohistochemical results showing that PPAR-γ, a marker gene for fatty infiltration, was significantly decreased in the APAP group (p < 0.001). Histological healing assessments between the 2 groups were not significantly different (p = 0.634). Additionally, mechanical strength was not negatively affected. Conclusions: APAP treatment was associated with prevention of supraspinatus fatty infiltration without adversely affecting TBI healing in an RC repair model. KCI Citation Count: 0